Very high frequency of fragility fractures associated with high-dose glucocorticoids in postmenopausal women: A retrospective study - Goichi Kageyama; Takaichi Okano; Yuzuru Yamamoto; Keisuke Nishimura; Daisuke Sugiyama; Jun Saegusa; Goh Tsuji; Shunichi Kumagai; Akio Morinobu (Bone Reports, 2017)
Purpose To evaluate the incidence of fragility fractures associated with high-dose glucocorticoid therapy in patients with systemic rheumatic disease. Methods: A retrospective study of patients who were treated with high-dose prednisolone (>0.8 mg/kg) for systemic rheumatic disease at Kobe University Hospital from April 1988 to March 2012. The primary outcome was a major osteoporotic fracture (defined as a clinical vertebral, hip, forearm, or proximal humerus fracture) after high-dose glucocorticoid therapy. For postmenopausal women and men over 40 of age, the patient's fracture risk at the beginning of high-dose glucocorticoid therapy was assessed by the World Health Organization's Fracture Risk Assessment Tool (FRAX®). Results Of 229 patients (median age: 49 years), 57 suffered a fragility fracture during the observation period (median observation period: 1558 days). Of 84 premenopausal patients, 5 suffered a fracture. In contrast, of 86 postmenopausal female, 36 suffered a fracture. Fragility fractures were far more frequent than predicted by the FRAX® score. Patients with FRAX® scores over 8.3% had a particularly high risk of fracture. Conclusions Fragility fractures associated with high-dose glucocorticoid therapy are common among postmenopausal women. Extreme care should be taken especially for postmenopausal women when high-dose glucocorticoid therapy is required.